Renewable Energy Consumption and International Trade: Does Climate Policy Stringency Matter? - Ridha Nouira; Leila Ben Salem; Sami Saafi; Christophe Rault (Institute of Labor Economics (IZA), 2025)
This study explores the link between renewable energy consumption and international trade, with a focus on climate policy. We argue that this relationship is nonlinear and shaped by threshold effects. Using a dynamic threshold model (Seo & Shin, 2016), we analyze data from 1990 to 2023 for 29 developed and developing countries. Our results show that climate policy plays a key role in shaping the renewable energy–trade nexus, with effects depending on policy stringency and development level. In developing countries, renewable energy use consistently boosts exports, regardless of policy stringency. In contrast, in developed countries, strict policies reduce import dependence–signaling energy independence–but may also weaken renewable energy's positive trade effects due to higher compliance costs and regulatory barriers. These findings call for tailored strategies: developed countries should balance ambitious climate goals with trade efficiency by easing regulatory burdens and promoting international policy coordination, while developing countries can use renewable energy to enhance exports, attract investment, and build technological capabilities.
Keywords: C5; F1; Q4; Q5; 330; climate policy stringency; international trade; renewable energy consumption; dynamic threshold model; sustainable development